Sustainable Crop Production In Tidal Lowlands: A Research Agenda - Khairul Fahmi Purba; Muhammad Yazid (Program Pascasarjana Universitas Sriwijaya, 2019)
Tidal lowlands bear enormous potential including crop production. However, tidal lowlands also have numbers of ecosystem functions that prevent them from exploitative uses. Therefore, tidal lowland utilization for crop production should consider measures to achieve sustainable development goals (SDGs) in one hand. In the other hand, SDGs should also ensure the sustainable use of tidal lowlands. This paper aims to review the sustainability of crop production in tidal lowland to support the achievement of SDGs, which are eliminating hunger, achieving food security with good nutrition, and improving sustainable agriculture. These goals need to be achieved in 2030 by ensuring sustainable crop production systems, applying tough agricultural practices, increasing production and productivity, and at the same time maintaining tidal lowland ecosystems. Therefore, this paper will review three major aspects as follows: (1) productive means of crop cultivation, (2) effective control of agricultural waste and pollutant, and (3) efficient use of agricultural inputs. This review is expected to yield sustainable measures of crop production in tidal lowlands to contribute to the achievement of sustainable development goals (SDGs).